Les miroirs médiévaux : réflexions génériques et genrées - Clémentine Girault; Jeanne Mousnier-Lompré (Perspectives Médiévales)
In Technologies of Gender (1987), Teresa de Lauretis proposed to conceive of gender as a relationship generated by "social technologies," among which the cinematic apparatus. This co-authored article suggests examining another optical device, both material and metaphorical: the literary mirror. Teresa de Lauretis had clearly identified the role of scholarly discourse in the (re)production of gender, and historiography dedicated to « mirrors » is no exception. Ignoring the question of gender, this discourse produces a gendered, binary, and asymmetrical reception of texts addressed to male and female audiences. While these texts aim to « engender » subjects through their prescriptive writing, the medieval educational treatises, both in the body of the text and in their materiality, present multiple facets that go beyond the gendered distribution of the initial address. It is in this « hors-champ » space, created by the libraries, the manuscripts and the « public », that gender categories can be transcended.